2020
DOI: 10.15252/emmm.201911908
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of circulating breast cancer cells with tumorigenic and metastatic capacity

Abstract: Functional studies giving insight into the biology of circulating tumor cells (CTCs) remain scarce due to the low frequency of CTCs and lack of appropriate models. Here, we describe the characterization of a novel CTC‐derived breast cancer cell line, designated CTC‐ITB‐01, established from a patient with metastatic estrogen receptor‐positive (ER+) breast cancer, resistant to endocrine therapy. CTC‐ITB‐01 remained ER+ in culture, and copy number alteration (CNA) profiling showed high concordance between CTC‐ITB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 91 publications
2
86
0
1
Order By: Relevance
“…Drug sensitivity screening using CTCs has been conducted in the past [ 27 , 28 , 55 ]. In 2014, Yu et al were the first to establish drug sensitivity testing on six stable CTC lines in vitro as well as in a xenograft mouse model in vivo [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drug sensitivity screening using CTCs has been conducted in the past [ 27 , 28 , 55 ]. In 2014, Yu et al were the first to establish drug sensitivity testing on six stable CTC lines in vitro as well as in a xenograft mouse model in vivo [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, further characterization of CTCs is still limited by the low number of CTCs [ 26 ]. The recent establishment of cell lines from CTCs of cancer patients has therefore opened a new avenue for functional analyses of CTCs [ 4 , 27 , 28 ]. The CTC-MCC-41 colon CTC line that we analyzed in this study was the first long-term stable CTC line established from a patient with colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, using a xenograft assay, Bacelli et al demonstrated that CTCs with a tumor-initiating phenotype (CD45 − , EpCAM + , CD44 + , CD47 + , MET + ) can produce metastases [ 109 ]. Similarly, Koch et al established an EpCAM + CTC line derived from breast cancer [ 112 ] and Faugeroux et al generated CTC-derived explant models by using EpCAM + CTCs isolated from blood samples of patients with castration-resistant prostate cancer ( Figure 2 ) [ 113 ].…”
Section: Epcam Expression On Metastasis-competent Ctcsmentioning
confidence: 99%
“…In vitro and in vivo models are essential to identify and characterize metastasis-competent CTCs. The successful expansion of this more aggressive subset of CTCs after negative selection showed a clear EpCAM-positive phenotype in different studies from independent research groups [ 105 , 106 , 107 , 108 , 109 , 112 , 113 ].…”
Section: Figurementioning
confidence: 99%
“…Within the last decades a range of methods have been developed to specifically isolate CTCs [53] and to cultivate these rare cells by optimized in vitro culture conditions such as spheroid and organoid cultures, or by in vivo transplantation into immunodeficient mice [54][55][56][57][58]. To date, the generation of CTC-derived models has been reported for melanoma, breast, colorectal, lung, gastroesophageal, pancreatic, and prostate cancer patients (Table 1) [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. CTC models from metastatic melanoma patients that recapitulate the patient's disease and responses to therapies have been developed, highlighting the power of such models as potential 'avatars' for testing personalized treatments in the future [60].…”
Section: Preclinical Models Representing Patient-derived Metastasis Fmentioning
confidence: 99%